Laparoscopic treatment of an abdominoscrotal hydrocele requiring concomitant laparoscopic ipsilateral inguinal hernia repair - Grayson Mast; Cody Lendon Mullens; Dan W. Parrish (Elsevier, 2021)
Failure of the processus vaginalis to obliterate during development leads to a gradient of pathologies including indirect inguinal hernia, communicating hydrocele, hydrocele of the cord, and noncommunicating hydrocele including Abdominoscrotal Hydrocele (ASH) and scrotal hydrocele. Relative to other pathologies related to the failure of processus vaginalis obliteration, few cases of ASH have been documented in the literature, resulting in discrepancy regarding the best management practices for this condition. In this paper we review the current literature and a case of ASH complicated by the development of an ipsilateral inguinal hernia in order to provide a concise review of how to diagnose, manage, and detect the potential complications of treating ASH surgically and display the utility of laparoscopy in managing this condition.